Cypher the Mountain Giant - Blade, Adam.; Tucker, Ezra N. (New York : Scholastic, 2007)
Tom and Elenna must face another beast, Cypher, the one- eyed giant who is causing mudslides and avalanches in the mountains of Avantia.
"A Little apple paperback."
Accelerated Reader AR
Keywords: Adventure and adventurers -- Juvenile fiction; Giants -- Juvenile fiction; Fantasy fiction; Adventure fiction